ACCRUAL-BASED ACCOUNTING ASSISTANCE FOR FINANCIAL LITERACY AMONG 12TH GRADE SOCIAL STUDIES STUDENTS AT MA TARBIYATUL MUSTAFID - Layali Ihyani; Sahdan Saputra; Abdul Muhid; Febria Nurmelia Marlina; Rina Komala; Ega Dwi Putri Marswandi (Universitas Mataram, 2026)
This community service program aimed to improve students’ understanding of accrual-based accounting through participatory socialization and practical simulation. The activity involved 54 students from XII IPS‑1 and XII IPS‑2 at MA Tarbiyatul Mustafid. The program was structured into three sessions: a theoretical presentation, a simulation of accrual-based transaction recording, and an interactive discussion. The evaluation results showed a significant improvement in students’ comprehension. The average pre‑test score of 45.2 increased to 78.6 in the post‑test. Prior to the activity, only 31% of students could distinguish between cash and accrual basis accounting, while after the activity, 73% were able to explain and apply accrual concepts in simple transaction cases. Both classes demonstrated consistent improvement, with average increases of +32.8 and +33.4 points. In practice, 85% of students successfully prepared accrual-based income statements for small business cases, although some still confused expenses and liabilities. Interactive discussions helped to correct these errors, reinforcing conceptual clarity. The findings confirm that direct practice with contextual case studies is more effective than purely theoretical learning methods.